TINJAUAN HUKUM ISLAM TERHADAP PROBLEMATIKA NAFKAH ANTARA ORANG TUA DAN ISTRI - Shalsabila Maharani; Husnul Khatimah (IAI DDI Mangkoso, 2024)
This study aims to examine the problem of maintenance between parents and wives in the context of Islamic law. The main focus of this research is to understand the concept, principles, and implementation of alimony between parents and wives according to the view of Islamic law. The research method used is a qualitative approach by conducting interviews with individuals who experience related problems. As well as the instruments used in this study, namely through literature studies obtained from journals or supporting articles. From the results of the research, two main points will be discussed, namely regarding alimony in Islam and the obligation to provide alimony to wives and parents. The results of the research are expected to contribute to increasing understanding of the legal aspects of maintenance in the relationship between parents and wives by Islamic values.